Major trends in the development of business activity in Belarus in the second half of the 19th – early 20th century (the case of Minsk) - Burachonak, Aliaksandr V. (Journal of the Belarusian State University. History, 2021)
The article provides analysis of major directions of entrepreneurship development in Minsk in late 19th – early 20th century, showcases dynamics of quantitative and qualitative changes in industry and trade. The paper uncovers level of credit business development as well as institutional changes in the economic life of Minsk in the post-reform period. The conclusions reveal influence of modernisation processes on the development of business activity in Minsk in the late 19th – early 20th century.
Keywords: entrepreneurship; Belarus; industry; trade; credit; modernisation; Russian Empire